SEJARAH PEMIKIRAN EKONOMI ISLAM DI INDONESIA - Azizah, Irtifa Umi; Aswad, Muhammad; Aqim Adlan, Muhammad (P3M dan Jurusan Syariah dan Ekonomi Bisnis Islam STAIN Sultan Abdurrahman Kepulauan Riau, 2025)
This research examines the history of Islamic economic thought in Indonesia, especially during the Kingdom, Dutch colonialism and after the proclamation of independence, as well as the role of several important figures who influenced these developments. During Dutch colonialism, Islamic economic thought experienced oppression and marginalization, because the colonial economic system dominated by Western capitalism hampered the development of Islamic economics. However, at the beginning of the 20th century, the rise of the modern Islamic movement in Indonesia also influenced Islamic economic thinking. This movement emphasizes the importance of reform in various aspects of life, including economic practices based on Islamic teachings. The methodology used in this research is qualitative with a literature study approach, and uses historical studies to explore differences in thought. The research results show that Islamic economic thinkers in Indonesia establish Islamic principles as the basis for achieving just and sustainable economic goals.